Infrared Spectroscopy - Perspectives and Applications 2023
DOI: 10.5772/intechopen.105736
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Near-Infrared Spectroscopy (NIRS) in Fish Value Chain

Abstract: Near-infrared spectroscopy (NIRS) has undergone a significant evolution in the last years due to the numerous scientific studies that revealed its potential for industrial applications, attracting a growing interest in the food sector. Furthermore, new advances have allowed the reduction in size and cost of the NIR devices, making them appropriate for on-site determinations. The complex structure of the fish value chain, combined to its high market value, makes this sector particularly vulnerable to fraud and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…In recent years, there has been an exploration of the application of NIRS to recognize different fishery species [16,19]. However, to date, research on species identification utilizing NIRS has predominantly focused on species within the Teleost infraclass.…”
Section: Classification By Speciesmentioning
confidence: 99%
“…In recent years, there has been an exploration of the application of NIRS to recognize different fishery species [16,19]. However, to date, research on species identification utilizing NIRS has predominantly focused on species within the Teleost infraclass.…”
Section: Classification By Speciesmentioning
confidence: 99%
“…Studies have shown that techniques such as machine vision and NIR spectroscopy achieve promising results in accuracy and rapidity. Nieto-Ortega et al [ 28 ] summarized the application of near-infrared spectroscopy in the fish value chain—proximate composition, freshness, species identification, farmed vs. wild fish and types of farming, geographical origin, unfrozen vs. frozen–thawed fish, fish safety, etc. The purpose of the present study was to determine the suitability of NIR spectroscopy for the rapid, cheap, and non-destructive detection of fresh and freeze–thawed fish and propose a classification model for applications in routine fish control.…”
Section: Introductionmentioning
confidence: 99%
“…Near infrared spectroscopy (NIRS) associated with chemometric techniques has been applied in agriculture for a long time (Pasquini, 2003;Nieto-Ortega et al, 2023). The main applications involve quality analysis and characterization of foods and soils (Cunha Júnior et al, 2015;Li at al., 2020;Sohn et al, 2021).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%